High-frequency generation during the electron flow deceleration and reflection by the electrostatic potential - Tarasov, M.I.; Pashchenko, A.V.; Sitnikov, D.A.; Romanov, S.S.; Shapoval, I.M. (Вопросы атомной науки и техники, 2013)
In this work we present the results of experimental study of generation of the RF-oscillations in a classic flat triode configuration for both presence and absence of the reflected particles flow. The amplitude and frequency characteristics are studied. The behavior of main characteristic parameters for both cases was analyzed and compared. Представлены результаты экспериментального исследования ВЧ-генерации в триоде в режимах с наличием и отсутствием отраженного потока. Исследуются амплитудные и частотные параметры. Проводится сравнительный анализ. Представлено результати експериментального дослідження ВЧ-генерації в тріоді в режимах з відсутнім та наявним потоком відбитих електронів. Досліджуються амплітудні та частотні характеристики. Проведено порівняльний аналіз.